Digital Literacy: Arabic Teacher Competencies in Distance Learning - Hamidah Hamidah; Adelina Dewi Nuryaman; Soukaina Samdouni; Aulia Mustika Ilmiani Aulia (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2022)
The transformation of learning statically requires teachers to adapt to technology to face significant changes, especially in terms of adoption of digital education. What the teacher provides is not only the transmission of learning materials, but also digital literacy to facilitate the needs of students according to conditions in the field. Based on preliminary data, it is known that Arabic language teachers at Madrasah Aliyah Nuruzholam, Seruyan Regency, Central Kalimantan experience problems in terms of limited ability in the field of learning technology. The research method used was descriptive qualitative method which aimed to describe the digital literacy competence of Arabic language teachers at Madrasah Aliyah Nuruzholam. The results of the study showed that the digital literacy competence of Arabic language teachers can be seen from the teacher's activities such as; First, teachers can use the internet and use Google as a medium for finding information. Second, teachers obtain information by using the internet, Third, familiar teachers use the YouTube application as a means of finding information or learning Arabic resources. Fourth, the teacher uses the information obtained as a source of learning Arabic without any validation of data processing.